Community structure of Crabs (Crustacea: Decapoda): Response to vegetation variation and environmental parameters in mangrove ecosystems - Putri Liani Aliwu; Baderan, Dewi Wahyuni K.; Regina Valentina Aydalina; Zuliyanto Zakaria; Marini Susanti Hamidun (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Mangrove ecosystems are crucial for maintaining biodiversity, including crab communities, which are vital to the stability of these ecosystems. Crabs contribute to nutrient cycling and the food web, reinforcing the overall ecological health of coastal habitats. This study focuses on the crab communities in the mangrove area of Tabongo Village, Dulupi District, Boalemo Regency, examining how environmental conditions affect their distribution and diversity. Methods: The research involved surveys at three stations representing different mangrove vegetation conditions. Crab species were identified and their diversity and abundance recorded. Environmental parameters, such as temperature, salinity, and pH, were measured, and the diversity index (H') was calculated to assess species diversity and the relationship between crab communities and environmental factors. Findings: A total of 11 crab species from 4 families were identified, including Uca (Paraleptuca) annulipes and Ocypode ceratophthalmus. The diversity index ranged from 1.3 to 1.6, indicating moderate diversity. Environmental conditions, with temperatures between 32–34 °C, salinity from 13–19 ppt, and pH from 6.5 to 7, were conducive to crab survival. Station III, with healthier mangrove vegetation, supported greater crab diversity and abundance compared to degraded stations. Conclusion: The study highlights the crucial role of healthy mangrove ecosystems in sustaining crab biodiversity and ecosystem stability. It underscores the importance of mangrove conservation for maintaining biodiversity and protecting coastal ecosystems from degradation. Novelty/Originality of this article: By linking the health of mangrove ecosystems to crab diversity and abundance, it emphasizes the direct impact of environmental factors on crab populations. The findings highlight the importance of mangrove conservation not only for species richness but also for maintaining the ecological balance in coastal ecosystems, offering valuable data for future biodiversity management and conservation efforts.